Irregular menstrual cycle in women of reproductive age as part of metropolitan syndrome - Elena N. Andreeva; Ekaterina V. Sheremetyeva (IP Berlin A.V., 2020)
Life in a modern metropolis is not only an interesting and eventful life, but also a source of numerous features for human life: imperfect environmental conditions, dietary habits, sleep disturbances and circadian rhythms, changes in psychological status (stress, depression, aggression, apathy) and reproductive health problems, especially in women. As defined by the World Health Organization, reproductive health is a state of complete physical, mental and social well-being, and not simply the absence of disease in all areas related to the reproductive system, its functions and processes. Life in a big city for a woman of the reproductive period is often accompanied by a violation of the menstrual and ovulatory function, which can be attributed to the symptoms of the megalopolis syndrome. Since the 1980s, the frequency of menstrual irregularities has increased by more than 7 times. The doctor clinician, to whom a woman of the reproductive period with an irregular menstrual cycle first turns, should not only draw up a plan for examining a woman and exclude the presence of endocrine-gynecological disorders, but also collect a detailed history, including physical status (for example, calculating body mass index, analyzing fluctuations weight), dietary habits, sports history, medication intake, first assess the role of the psychosomatic factor. The correct pathogenetic approach in this situation will determine the correct therapeutic tactics for managing a woman.